Historical Archaeologies of Capitalism
XIV, 248 p.
Keywords: American things, American material culture, and American archaeology are the themes of this book. The authors use goods used or made in America to illuminate issues such as tenancy, racism, sexism, and regional bias. Contributors utilize data about everyday objects - from tin cans and bottles to namebrand items, from fish bones to machinery - to analyze the way American capitalism works. Their cogent analyses take us literally from broken dishes to the international economy. Especially notable chapters examine how an archaeologist formulates questions about exploitation under capitalism, and how the study of artifacts reveals African-American middle class culture and its response to racism.